Analisis Pengaruh Variasi Suhu Pirolisis Terhadap Rendemen, Nilai Kalor, dan Densitas Bahan Bakar Cair dari Limbah Plastik Polypropylene (PP) - Yudha Aditya Pratama; Asroful Abidin; Mokh. Hairul Bahri (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing amount of polypropylene (PP) plastic waste has become an environmental challenge that requires effective management. One promising technology to address this issue is pyrolysis, a thermal decomposition process carried out in the absence of oxygen that converts plastic waste into valuable liquid fuel. This study aimed to analyze the effect of pyrolysis temperature on the yield, calorific value, and density of liquid fuel produced from polypropylene plastic waste. The pyrolysis process was conducted using a batch reactor with a feedstock mass of 1.25 kg for 60 minutes at temperatures of 300°C, 400°C, and 500°C. The calorific value was determined using a Bomb Calorimeter, while the density was measured using the pycnometer method. The results showed that pyrolysis temperature significantly influenced the characteristics of the liquid fuel produced. The highest calorific value was obtained at 300°C, reaching 38,022.85 J/g (9,087.68 cal/g), which decreased to 33,538.23 J/g (8,015.83 cal/g) at 400°C and further declined to the lowest value of 3,798.05 J/g (907.76 cal/g) at 500°C. Meanwhile, the density values obtained at 300°C, 400°C, and 500°C were 1.028 g/mL, 1.011 g/mL, and 1.031 g/mL, respectively. Based on these findings, a pyrolysis temperature of 300°C produced the highest-quality liquid fuel in terms of calorific value, whereas 400°C yielded a density that was closest to the characteristics of commercial liquid fuels